Anticorrosive properties of silicotungstic acid and phosphotungstic heteropoyacid in paint films - Nechvílová, Kateřina; Kalendová, Andréa; Stejskal, Jaroslav (CHEMagazín, s.r.o., 2016)
The aim of this work was to provide an initial characterisation of heteropolyacids and examine their behaviour and properties as pigments in paints using different concentrations of the pigment and filler. Solvent-based epoxy-ester resin served as the binder. The paints were applied to steel and glass panels for mechanical and corrosion resistance testing. The organic coatings were exposed to a corrosive atmosphere with NaCl. This test was completed with electrochemical measurement. The parameters examined included the paint film's mechanical and anticorrosion efficiency. The environments in which the new coatings are most efficient were also sought.
Antikorozní vlastnosti křemičitowolframové a fosfowolframové heteropolykyseliny v nátěrových filmech
Keywords: Heteropolyacids; epoxy-ester resin; organic coatings; heteropolykyseliny; epoxyesterová pryskyřice; organický povlak